2002
DOI: 10.3141/1817-07
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Visualization into Structured Public Involvement: Case Study of Highway Improvement in Central Kentucky

Abstract: Public involvement in transportation infrastructure decision making is frequently mandated and is regarded as increasingly essential by a wide variety of stakeholders. The integration of advanced technologies, such as visualization, into this process is increasingly desired. However, public involvement processes often are regarded as problematic by many stakeholders and the state highway agencies charged with implementing them. Structured public involvement (SPI) is posited. SPI takes a systems approach toward… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 7 publications
0
14
0
Order By: Relevance
“…In [14], a model was developed for the highway to display properties of alternative solutions. The findings of study [15] also demonstrated that 3D modelling with corresponding analysis can improve significantly the performance of highway improvement. According to the results of study [16], the 3D visualization of the proposed project can increase users' understanding and help them obtain detailed information about the project and its context.…”
Section: Previous Work About Highway Designmentioning
confidence: 74%
“…In [14], a model was developed for the highway to display properties of alternative solutions. The findings of study [15] also demonstrated that 3D modelling with corresponding analysis can improve significantly the performance of highway improvement. According to the results of study [16], the 3D visualization of the proposed project can increase users' understanding and help them obtain detailed information about the project and its context.…”
Section: Previous Work About Highway Designmentioning
confidence: 74%
“…The ASERT framework emphasizes the presentation of relevant and accessible information, coupled with the use of two-way communication and deliberative and participatory mechanisms. The deliberative and participatory components of the ASERT framework build on the Structured Public Involvement approach that has been applied in high-conflict decision-making contexts such as environmental and transportation planning (Bailey et al, 2002(Bailey et al, , 2007(Bailey et al, , 2011.…”
Section: Pgis Demonstration Projectmentioning
confidence: 99%
“…This feedback allows planner to accurately assess the level of understanding the public has on a particular project. A positive signal occurs when the public begins to supply useful and insightful comments regarding a proposed activity (8).…”
Section: Public Involvement In Transportationmentioning
confidence: 99%